Crossover study of immunoglobulin replacement therapy in patients with low-grade B-cell tumors. - Griffiths, H; Brennan, V; Lea, J; Bunch, C; Lee, M; Chapel, H (1989)
A randomized crossover study of prophylactic immunoglobulin (IgG) therapy was performed in patients with chronic lymphocytic leukaemia (CLL) or non-Hodgkin's lymphoma (NHL). Twelve patients with hypogammaglobulinemia or a history of recurrent infections received infusions of IgG or placebo intravenously (IV) every 3 weeks for 1 year. They were then switched to the alternative preparation for another year. The number of serious bacterial infections was significantly less (P = .001; Mainland's cross-over method) in the months in which patients received IgG. Serious bacterial infections showed a trend to be associated with an IgG level less than 6.4 g/L (P = .046; Fisher's exact test).